Analysis of Science Learning Implementation in the Implementation of the Independent Curriculum at the Junior High School Level - Juwita Cristina Situmeang; Novia Nababan; Mariati Simanjuntak (Program Studi Pendidikan Biologi FKIP Unpatti, 2026)
This study aims to analyze the implementation of science education in the Merdeka Curriculum at the junior high school level. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. This study examines the learning tools, learning resources and media, and strategies applied by teachers in learning activities. The results of the study show that the implementation of science learning in the Merdeka Curriculum still encounters various obstacles, such as learning that tends to be teacher-centered, lack of utilization of laboratories and technology-based media, and teaching tools that are not fully in line with the principles of differentiation and project-based learning. Nevertheless, teachers try to adapt to the curriculum requirements by using Merdeka Curriculum textbooks and conducting simple discussions in class. This study concludes that the implementation of the Merdeka Curriculum in science learning requires support in the form of improving teacher skills, providing technology-based learning media, and developing innovative and contextual teaching tools. In this way, science learning can be more dynamic, meaningful, and in line with the characteristics of learning in the 21st century